2019
DOI: 10.18176/jiaci.0320
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain and Itch Mechanisms Underlying Allergic Conjunctivitis

Abstract: Current management goals of allergic conjunctivitis aim to minimize the inflammatory cascade associated with allergic response in the initial stages of the pathological mechanism. Based on the mechanistic data reviewed herein, the recognition that neuronal inflammation explains many of the symptoms in allergic conjunctivitis opens new frontiers for drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
(60 reference statements)
0
23
0
Order By: Relevance
“…e condition is often classified as seasonal allergic conjunctivitis (SAC), perennial allergic conjunctivitis (PAC), atopic keratoconjunctivitis (AKC), vernal keratoconjunctivitis (VKC), and giant papillary conjunctivitis (GPC) [1,20,21]. 2 immune responses and type I hypersensitivity reactions are generally considered the basis of occurrence of AC [22]. An European Academy of Allergy and Clinical Immunology (EAACI) task force suggested to include "ocular allergy" in the "ocular surface hypersensitivity disorders," dividing the different forms into IgE-mediated and non-IgE-mediated diseases [20,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e condition is often classified as seasonal allergic conjunctivitis (SAC), perennial allergic conjunctivitis (PAC), atopic keratoconjunctivitis (AKC), vernal keratoconjunctivitis (VKC), and giant papillary conjunctivitis (GPC) [1,20,21]. 2 immune responses and type I hypersensitivity reactions are generally considered the basis of occurrence of AC [22]. An European Academy of Allergy and Clinical Immunology (EAACI) task force suggested to include "ocular allergy" in the "ocular surface hypersensitivity disorders," dividing the different forms into IgE-mediated and non-IgE-mediated diseases [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…So, they have a significant impact on the quality of patient's life and affect social economy [30]. Although VKC and AKC account for only 2% of ocular allergy cases, they have a greater impact on life [22]. Unlike SAC and PAC, VKC and AKC appear as corneal involvement.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Additionally, similar symptoms have been observed in patients with allergic conjunctivitis and blepharoconjunctivitis. 12,13 Furthermore, wearing glasses might prevent respiratory droplet transmission, but might also cause more contact with the face. Th ere is a study…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that TRPA1 might also be involved in allergic conjunctivitis [75]. Compared to wild-type animals, TRPA1 deficient mice show fewer symptoms in a model of allergic conjunctivitis [76].…”
Section: Potential Disease—modification Through Trpa1 Modulationmentioning
confidence: 99%